PENYELESAIAN MASALAH LINGKUNGAN HIDUP MELALUI GUGATAN CITIZEN LAWSUIT (STUDI KASUS PUTUSAN PERKARA NOMOR 18/PDT.G/LH/2016/PN.PLK) - Fama Flavia, - (2019)
The Citizen Lawsuit is one type of lawsuit that can be used to solve environmental problems by enforcing civil law which postulates the existence of Unlawful Acts committed by the Government. So this research aims to find out how to solve Government problems and responsibilities related to environmental problems that were resolved through a lawsuit by Citizen Lawsuit. The research method used is normative juridical research, research that uses library data. Settlement of environmental issues with the lawsuit of Citizen Lawsuit in its use does not yet have a legal basis and regulation in its application but has been used several times in Indonesia and related to environmental problems used by the people of Central Kalimantan to resolve the haze problem in the area. Although there is no legal basis yet, the lawsuit filed by the community must still be resolved and in this case the Government as the Defendant if proven guilty must be responsible for the Acts Under the Law he did